Internal Quality Assurance Systems for Globally Competitive Universities - Wu Yilin; Linda Ika Mayasari; Kamaludin Kamaludin (Teunuleh Publisher, 2026)
Global competition within the higher education sector necessitates that universities enhance their internal quality assurance systems to elevate academic quality, institutional performance, and international reputation. Nonetheless, numerous universities encounter difficulties in aligning quality assurance processes with strategies aimed at achieving global competitiveness. This study seeks to examine the role of the Internal Institutional Quality Assurance System (IIQAS) in facilitating the attainment of a globally competitive university reputation at Northeast Petroleum University (NEPU), China. A quantitative approach was adopted, utilizing a survey design with 120 respondents, including lecturers, academic support staff, and quality assurance personnel. Data collection was conducted via a five-point Likert scale questionnaire, and analysis was performed using SPSS version 26, employing descriptive statistics, reliability tests, Pearson’s correlation analysis, and multiple linear regression. The findings demonstrate that the implementation of the PDCA-cycle-based IIQAS is categorized as high, with the 'Plan' dimension achieving the highest average score of 4.12. Indicators of global competitiveness also yielded positive outcomes, particularly in teaching quality (4.10) and research productivity (4.02). Correlation analysis indicated that all PDCA dimensions exhibited a positive and significant relationship with global competitiveness, while regression analysis revealed that IIQAS accounted for 65.9% of the enhancement in the university’s competitiveness. The novelty of this study resides in the integration of a PDCA-based internal quality assurance framework with global competitiveness indicators within the context of Chinese universities. The study concludes that the effective implementation of IIQAS functions as a strategic tool for improving institutional quality and bolstering universities’ competitiveness on a global scale.